PTU-063 Faecal calprotectin – time to re-draw the line. (17th June 2017) - Patel, RN; Gyawali, P; Clough, V; Khatami, Z
Abstract : Introduction: Faecal calprotectin (FCP) is a useful investigation for supporting a diagnosis of inflammatory bowel disease (IBD) or irritable bowel syndrome (IBS) (1). The cut off for a positive result remains controversial and has a significant impact on prompting invasive procedures and use of health care resources (2). We reviewed the impact of a local IBS/IBD pathway on patient outcomes and sought an evidence based threshold for a positive FCP result. Method: We reviewed the FCP requests sent by primary care physicians in Barking, Havering and Redbridge University Trust (BHRUT) from November 2015 to March 2016. BHRUT uses a quantitative fluorescence enzyme immunoassay (FEIA); EliA Calprotectin 2. Initial thresholds for negative and indeterminate FCP results were set at <30 ug/g and 30–75 ug/g, respectively. Repeat requests were reviewed from July 2015 to August 2016. 1 way-ANOVA analysis to compare the distribution of FCP data according to locality and gender was performed. FCP and endoscopic findings were paired retrospectively. Results: 1157 FCP requests were made between 09/11/15 and 31/03/16 with a female preponderance (60.9%). 26% of requests were inappropriate for age (<18 years or >60 years). Of 50 patients in the indeterminate group (30–75 ug/g), 9 were referred to gastroenterology (18%). 7 (77.8%) patients had a colonoscopy and none were diagnosed with IBD. Between July 2015 and August 2016; 93 FCP results that were negative or indeterminate were paired with their repeat samples. 78 (83.9%) remained <75 ug/g. None of the remaining 15 patients (16.1%) with an interval change to positive were diagnosed with IBD. 11 (73.5%) were not referred to gastroenterology, discharged or had a normal colonoscopy. Reasons for FCP request (Table 1) Conclusion: The FCP threshold of 50 ug/g suggested by NICE is obtained from pooled data using a variety of methods and should not be applied universally across hospital trusts. No patients at BHRUT with an FCP in the indeterminate range had evidence of IBD at colonoscopy. We suggest increasing the positive cut-off level for referral to gastroenterology to >75 ug/g. Repeating an indeterminate result did not change the initial diagnosis. Greater awareness of age appropriate FCP requests is required in primary care with older patients allocated to an alternative pathway. References: . Faecal calprotectin diagnostic tests for inflammatory diseases of the bowel. Diagnostics guidance [DG11]. National Institute for Health and Care Excellence. Published date: October 2013. . Faecal Calprotectin testing in Primary Care. NHS Technology Adoption Centre. Published date: April 2013. Disclosure of Interest: None Declared